Interactive ICD-10-Based Morbidity Dashboard Using BPJS Central Data: A Case Study of Karanganyar Regency - Wahyu Wijaya Widiyanto; Ade Amallia; Astri Sri Wariyanti (Jurnal Ners, 2025)
The increasing complexity of disease trends in the post-pandemic era necessitates more accessible and data-driven decision-making tools, particularly in primary healthcare services. This study aims to develop an interactive morbidity dashboard based on ICD-10 classifications using secondary data from BPJS Kesehatan. The research focuses on outpatient visit records in Karanganyar Regency from 2020 to 2024. A descriptive quantitative approach was applied, accompanied by system development using Python. Data preprocessing involved standardizing ICD-10 codes, handling missing values, and grouping by year, gender, and age category. The resulting dashboard allows users to filter morbidity trends based on demographic variables and disease categories. The ten most prevalent disease groups include respiratory, digestive, endocrine, and circulatory disorders. This dashboard facilitates data-based decision-making and enables targeted promotive and preventive interventions in primary healthcare facilities.